Improving Javanese Letter Reading Skill through the Iqro Script Method - Nggofur, Achmad Abdul; Dwijonagoro, Suwarna (International Journal Corner of Educational Research, 2022)
This study aims to improve reading skills through the application of the Iqro 'method and in particular to determine the improvement of students' skills in reading Javanese characters in class VII students of SMPN 1 Banyudono Boyolali. The subjects of this study were teachers and students of class VII SMPN 1 Banyudono Boyolali, while what was observed in this study was fluency and thoroughness which led to students' skills in reading Javanese script and student activities in learning. Data collection techniques are carried out through observation, interviews, tests, and documentation. The data were analyzed using an interactive analysis model which consisted of examining all the data that had been collected, reducing the data, and making conclusions. The results showed an increase in reading skills. Prior to the implementation of the measures obtained by the average value of 63.03 with 29% completeness study, in the first cycle the average value obtained with mastery learning 68.07 79%, and the second cycle increased reading skills significant value an average of 74.96 and mastery learning 93%. Based on the results of this study, it was concluded that learning with the application of the Iqro 'Aksara method could improve the reading skills of Javanese script students of class VII SMPN 1 Banyudono Odd Semester 2022/2023.